Longitudinal Pulmonary Function After Surgical Treatment of Early-Onset Scoliosis - Scott Yang, MD; Apeksha Gupta, MS, MPH; Michael E. Trask, BS; Natalie M. Maharaj, BS; Anna V. Faino, MS; Sean Pirkle, MD; Kelson Roy Adcock, BS; Jennifer M. Bauer, MS; Burt Yaszay, MD; Gregory Redding, MD (JBJS Open Access)
Background:. Longitudinal pulmonary outcomes after surgical treatment of early-onset scoliosis (EOS) are not well reported. This study aims to evaluate change in serial pulmonary function in children with EOS after surgery. Methods:. A retrospective review was performed at a single academic hospital. All patients who had surgical treatment of EOS and repeated pulmonary function test (PFT) data were included. Pulmonary function test (PFT) measures included forced vital capacity (FVC), FVC % of predicted norms (FVC%), forced expiratory volume in 1 second (FEV1), and FEV1% of predicted norms (FEV1%). To determine whether PFT changed postsurgery, a random-effects mixed model was used. Predicted marginal means of PFT measures were calculated, and Bonferroni adjusted p-values were reported. Spearman correlation was used to analyze the relationship between radiographic measures and PFTs. Results:. Fifty-one patients with EOS were included (mean age 7.2 years at index surgery). The index distraction-based growth-friendly construct was 31 (60.8%) vertical expandable prosthetic titanium rib implants, 9 (17.6%) traditional growing rods, and 11 (21.6%) magnetically controlled growing rods; 23 patients (45%) underwent final fusion. The median duration from the first to the most recent PFT was 44 months. The random-effects model showed no significant change in FVC, FVC%, and FEV1 over time since surgery. When changes in PFTs were analyzed by scoliosis etiology, there was no significant change in PFT measures after surgical treatment with any etiology except in congenital scoliosis where both FVC% and FEV1% significantly decreased during growth-friendly treatment and fusion compared with before surgery. T1-T12 length significantly correlated moderately with FVC (rho = 0.46, p < 0.0001), but not FVC%. Major curve Cobb angle did not significantly correlate with PFT measures. Conclusions:. Growth-friendly EOS surgery did not improve pulmonary function, but at best prevented further pulmonary decline, except in children with congenital scoliosis who had worsening function over time. Level of Evidence:. Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.